Confronting the drug control establishment : Alfred Lindesmith as a public intellectual - Keys, David P.; Galliher, John F. (Albany, N.Y. : State University of New York Press, 2000)
"Confronting the Drug Control Establishment is a biography of Alfred R. Lindesmith and an intellectual history of his times. A sociologist at Indiana University, Lindesmith believed legal prohibition of addictive drugs was futile and wrote widely on the threat to democracy inherent in such a policy." "Throughout his life Lindesmith attempted to utilize his research for the creation of more rational and humane drug control laws. His consistent message was that the addict's self-concept is a central element in human addiction. Lindesmith felt that an overriding influence on an addict's self-concept is a fear of withdrawal, which keeps an addict from seeking treatment and becomes a key driving force in the drug problem."--Jacket
Origins and overview of the professional life of Alfred Ray Lindesmith -- Lindesmith's experience in the Chicago School of Sociology: the influence of Herbert Blum ... -- A revised theory of opiate addiction and the writing of the book Opiate addiction -- Contributions to psychotherapy, social psychology, and symbolic interaction -- Lindesmith versus Anslinger: efforts to reform national drug policy, 1937-1950 and the film Drug addict -- Writing The addict and the law: a statement of policy -- Public discourse: Lindesmith in the role of humanist citizen and public intellectual.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Lindesmith, Alfred Ray, -- 1905-1991.; Lindesmith, Alfred Ray, -- 1905-; Lindesmith, Alfred Ray, -- 1905-1991; Lindesmith, Alfred Ray; Social psychologists -- United States -- Biography; Sociologists -- United States -- Biography; Opium abuse; Drug legalization -- United States; Opioid abuse; Social psychology; Sociology; Sociologists -- United States -- Biography; Drug and Narcotic Control; Opioid-Related Disorders; Psychology, Social; Sociology; United States; Psychosociologues -- États-Unis -- Biographies; Sociologues -- États-Unis -- Biographies; Opiomanie; Drogues -- Légalisation -- États-Unis.; Sociologues -- États-Unis -- Biographies; Toxicomanie aux opiacés.; Psychologie sociale; Sociologie; social psychology; sociology; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists; SOCIAL SCIENCE -- Regional Studies; SOCIAL SCIENCE -- Anthropology -- General; Sociology; Social psychology; Opioid abuse; Drug legalization; Opium abuse; Social psychologists; Sociologists; United States; Drogenpolitik; USA; Biography; Biographies; Biographies; Biographies